A review on 3D printing bio-based polymer composite - L., Sandanamsamy; J., Mogan; N. A., Halim; W. S. W., Harun; K., Kadirgama; D., Ramasamy (IOP Publishing, 2021)
Polymers play a vital role in our daily lives. In various fields such as medical, food industry and automotive applications, the use of biopolymers is commonly used. The most widely used polymers and fillers among biopolymers are polylactic acid (PLA) and cellulose, which are biocompatible and biodegradable due to their eco-friendly properties. Extensive usage of cellulose in various forms has been applied in combination to PLA but there is only a few research that has been done by using the 3D printing method. This paper covers the types of biodegradable biopolymer materials, types of coupling agents and plasticizers, mechanical properties and applications. This paper discusses the types of cellulose ranging from micro to nano, including other types and sources of cellulose that have been researched and are compatible with PLA. In order to generate biocompatible polymers with stronger and better mechanical properties, the findings of these experiments are all tied together. These biopolymers are commonly used in the biomedical industry and are expected to improve their benefits in this field.